Factors Related to Incidence of Malnutrition in Toddler at The Tena Teke Health Center - Pandak, Regina Soli; Talahatu, Anna; Limbu, Ribka (Timorese Journal of Public Health, 2021)
Malnutrition is a condition where nutritional intake is insufficient to meet metabolic needs, with nutritional status based on body weight index for age (BB/U<-3SD). Malnutrition has a negative impact on physical and mental growth, reduces body resistance, intelligence and even causes disability and increases morbidity and mortality. This study used a case-control research design with a ratio of 1:1. The sample used was 50 selected by simple random sampling consisting of 25 cases and 25 controls. Analysis of the data used is a simple logistic regression analysis using statistical tests with a significance level of = 0.05. Mother's education showed a value (p = 0.002 OR value 0.107), mother's knowledge (p = 0.001 OR value 0.091) toddler eating habits consisted of main meals (p = 0.025 OR 0.259), breakfast (p = 0.045 OR 0.219), snacks (p=0.013, OR 0.291), family food availability (p=0.002, OR 576.000), and a history of infectious diseases (p=0.005, OR 22.154). From the results of the research, some respondents showed that there was a significant relationship between poor nutrition and maternal education, knowledge of maternal health nutrition, eating habits of children under five, availability of family food and infectious diseases. This is indicated by the results of a simple logistic regression analysis. Mothers must also take advantage of existing health services and pay attention to the nutritional intake of toddlers to prevent malnutrition.